Respuesta :
Answer:
x=0 and y= -2
Step-by-step explanation:
−5x+y=−2for y:
−5x+y=−2
−5x+y+5x=−2+5x(Add 5x to both sides)
y=5x−2
5x−2foryin−3x+6y=−12:
−3x+6y=−12
−3x+6(5x−2)=−12
27x−12=−12(Simplify both sides of the equation)
27x−12+12=−12+12(Add 12 to both sides)
27x=0
x=0
Substitute0 for X in y=5x−2:
y=5x−2
y=(5)(0)−2
y=−2(Simplify both sides of the equation)
Make y subject:
y = -2 + 5x
Sub into other equation as y:
-3x + 6(-2 + 5x) = -12
-3x -12 + 30x = -12
27x = 0
x = 0
Sub in X to find Y:
-5(0) + y = -2
y = -2
y = -2 + 5x
Sub into other equation as y:
-3x + 6(-2 + 5x) = -12
-3x -12 + 30x = -12
27x = 0
x = 0
Sub in X to find Y:
-5(0) + y = -2
y = -2